Black and white labor market outcomes in the 19th century American South - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2007)
Modern labor studies consider the relationship between wages and biological markers. A relevant historical question is the relationship between occupational status and biological markers. This study demonstrates that 19th century stature and BMIs were significant in Texas occupation selection; however, stature and BMIs were not significant in the decision to participate in the Southwest's labor market. In the post-bellum south, labor markets were segregated, and white laborers were at a distinct occupational and social advantage relative to their black counterparts. It is documented here that the probability of being farmers and unskilled workers were comparable by race. However, whites had greater access to white-collar and skilled occupations.
Keywords: J15; J24; J70; N31; 330; Erwerbsstatus; Gesundheit; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Farbige Bevölkerung; USA (Südstaaten)